2018
DOI: 10.5194/isprs-annals-iv-4-w7-59-2018
|View full text |Cite
|
Sign up to set email alerts
|

Interactive Spatial Web-Applications as New Means of Support for Urban Decision-Making Processes

Abstract: <p><strong>Abstract.</strong> Citizen participation, co-creation &amp;ndash; a joint development of professionals and citizens &amp;ndash; initiatives for urban planning processes have increased significantly during the last few years. This development has been strongly supported by the evolution of Information and Communication Technologies (ICT). E.g., it has never been easier to get information through your mobile devices wherever and whenever you want it. Public open spatial data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Participants indicated that the proposed method of statistical paired site comparison is a promising technique which could help to address the discussed barriers. Specifically, the reliance on publicly available datasets can leverage spatial open government data to the benefit of the CBM field, especially as this resource is typically underused outside of the scope of "expert" research projects [46] while remaining accessible.…”
Section: Prototype Modifications and Implicationsmentioning
confidence: 99%
“…Participants indicated that the proposed method of statistical paired site comparison is a promising technique which could help to address the discussed barriers. Specifically, the reliance on publicly available datasets can leverage spatial open government data to the benefit of the CBM field, especially as this resource is typically underused outside of the scope of "expert" research projects [46] while remaining accessible.…”
Section: Prototype Modifications and Implicationsmentioning
confidence: 99%
“…With the application of GIS in various fields, such as resources and environment, people gradually have a strong awareness of the proportion of spatial information in global information concentration, and various advantages of GIS gradually appear in front of people [15]. For example, GIS has a rich variety of software and application systems and has special features in the format, processing, and display of spatial data.…”
Section: Introductionmentioning
confidence: 99%
“…The performance is measured in two aspects: spatial accuracy and run-time. The former DBMS has a natural linkage with QGIS due to its relational structure, whereas the latter is non-relational DBMS (NoSQL) that is commonly used in web-based applications (Gebetsroither-Geringer et al, 2018). In order to make the experimental results repeatable and improve their development, the source code of this research is shared on GitHub .…”
Section: Introductionmentioning
confidence: 99%